GPETAFLR, a peptide from Lupinus angustifolius L. prevents inflammation in microglial cells and confers neuroprotection in brain. (4th March 2022) - Lemus-Conejo, Ana; Millan-Linares, Maria del Carmen; Toscano, Rocio; Millan, Francisco; Pedroche, Justo; Muriana, Francisco J. G.; Montserrat-de la Paz, Sergio
ABSTRACT: Objectives: Neuroinflammation is a complex inflammatory process in the central nervous system (CNS) where microglia may play a critical role. GPETAFLR is a peptide isolated from Lupinus angustifolius L. protein hydrolysates with functional activity in mononuclear phagocytes. However, it is unknown whether GPETAFLR has neuroprotective effects. Methods: We analysed the potential anti-neuroinflammatory activity of GPETAFLR by using two different models of neuroinflammation: BV-2 microglial cells and mice with high-fat diet (HFD)-induced obesity. Results: GPETAFLR hampered LPS-induced upregulation of pro-inflammatory and M1 marker genes in BV-2 cells. This effect was accompanied by an unchanged expression of anti-inflammatory IL-10 gene and by an increased expression of M2 marker genes. GPETAFLR also increased the transcriptional activity of M2 marker genes, while the microglia population remained unchanged in number and M1/M2 status in brain of mice with high-fat diet (HFD)-induced obesity. Furthermore, GPETAFLR counteracted HFD-induced downregulation of IL-10 and upregulation of pro-inflammatory markers in the mouse brain, both at gene and protein levels. Discussion: This is the first report describing that a peptide from plant origin robustly restrained the pro-inflammatory activation of microglial cells in cultures and in brain. Our data suggest that GPETAFLR might be instrumental in maintaining CNS homeostasis by inhibiting neuroinflammation. GRAPHICAL ABSTRACT: UF0001